Econometric Accounting of the Australian Corporate Tax Rates - Feeny, S.; Gillman, M.; Harris, Mark (Emerald, 2006)
The paper presents an econometric accounting of the effective corporate tax rate in Australia for the years 1993 to 1996. The estimation is a panel of Australian firms that uses a specially gathered financial data base. Using fixed and random effects, the model specifies that the statutory tax rate is estimated as the constant term of the model. An ability to find an estimated statutory tax rate that is close to the actual rate suggests a certain confidence in the estimated effects of the others factors affecting the effective tax rate. The results show importance for interest expenses, depreciation allowances, debt/asset structures, and the foreign ownership of firms. There is support for an Australian role as a preferential tax location.